The Influence of Brand Awareness, Perceived Quality, Brand Association, Brand Loyalty on Purchase Intention Towards Bear Brand’s Consumers - Averina Patoding, Agatha; Oktafalia Marisa Muzammil (Dinasti Publisher, 2023)
This study aims to determine the influence of brand awareness, perceived quality, brand association, and brand loyalty on purchase intention towards Bear Brand’s consumers. This study uses primary data and the data used in this study were obtained. The data in this study were processed using the SPSS version 24 application. This study used a sample of 182 respondents who were Bear Brand's Consumers. The results of testing the hypothesis with the t-test explain that partially brand awareness, brand associations, and brand loyalty have a positive and significant effect on purchase intention. Meanwhile, perceived quality has no significant effect on purchase intention. In the results of the Anova test, it is known that there is an influence of brand awareness, perceived quality, brand associations, and brand loyalty on purchase intention in consumers of Bear Brand milk.